Echinoderms as a Bioindicator of Water Quality of Weda Waters, Central Halmahera District - Juniartin, Juniartin; Tabaika, Rosita; Umagap, Wirda Az; Muna, Lintal (Bioma : Jurnal Ilmiah Biologi, 2023)
Echinoderms are deposit feeders that digest most of the sediment. Echinoderms are also good aquatic bioindicators, because Echinodermata are relatively calm or have low mobility, so they are highly influenced by environmental factors. This study aimed to determine the community structure of Echinoderms and their distribution relationship with several aquatic physico-chemical factors. Echinodermata sampling was carried out using the belt transect method using three stations. Data were collected in the form of the number of echinoderms in the transect and physico-chemical parameters of the waters including temperature, salinity, turbidity, pH, dissolved oxygen, ammonia, nitrite, and nitrate. From the results of research at three station points in the waters of Weda waters, 9 species of Echinodermata were found, namely Protoreaster nodosus, Linckia laevigata, Culcita novaeguineae, Diadema setosum, Diadema savigny, Echinometra mathaei, Tripneusteus gratilla, Holothuria atra, Holothuria edulis which were grouped into 3 classes, 4 orders, 6 families, and 7 genera with a total of 139 individuals. The diversity index of Echinodermata in Weda waters was classified as moderate with an average value of 1.05, the uniformity index was classified as moderate with an average value of 0.56, and the average dominance index value was 0.28 meaning that no species dominated